Out came the sun [large type] : overcoming the legacy of mental illness, addiction, and suicide in my family - Hemingway, Mariel (Center Point Large Print, 2015)
"A moving, compelling memoir about growing up and escaping the tragic legacy of mental illness, suicide, addiction, and depression in one of America's most famous families: the Hemingways"--